Meteorological Conditions for the Variability of 7Be and 210Pb Concentrations in Surface Layer Air in Poland - Krajny, Ewa; Osrodka, Leszek; Wojtylak, Marek (Journal of Environmental Science and Engineering Technology, 2014)
The aim of this study was to determine the effect of meteorological factors on the concentration of beryllium 7Be and lead 210Pb in the surface layer air on background their variability due to environmental conditions. Data analysis was carried out for 13 Polish stations for the period 2005-2009. The measurement cosmogenic and terrestrial radioactivity were collected on network station type ASS-500. The analysis includes the following meteorological elements from NWS stations: temperature, precipitation, atmospheric pressure, wind speed, humidity, solar radiation and in addition number of sunspots (SSN). It was considered that these meteorological elements mainly responsible for the transport and removal processes of 7Be and 210Pb from the atmosphere. The study method was used correlation analysis. Because of the relatively small area of Poland, it is hard to prove the dependence of 7Be activity concentration variability on the influence of such factors as geographical location or SSN. However, the activity concentration of 7Be and 210Pb are dependent on meteorological conditions. The inverse interaction of atmosphere stability conditions on 7Be and 210Pb allows one to use the 7Be/210Pb ratio as an indicator of vertical transport in the atmosphere.